2015
DOI: 10.1074/jbc.m115.639625
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of Stathmin Is Required for the Phenotypic Changes and Classical Activation of Macrophages

Abstract: Background: Macrophage activation involves pronounced microtubule (MT) stabilization. Results: Stathmin is degraded to enhance MT stabilization and allow robust activation in IFN␥-LPS-stimulated macrophages. Conclusion: MT stabilization by reduced stathmin levels is required for enhanced phagocytosis, signal transduction, and activation of macrophages. Significance: Understanding the nature and mechanisms of MT stabilization in activated macrophages is important for both immunology and cell biology fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 93 publications
0
9
0
Order By: Relevance
“…Consistent with this idea, stabilizing MTs by Taxol treatment leads to the formation of membrane protrusions evenly distributed around the cell perimeter rather than mainly at the cell front ( Schiff and Horwitz, 1980 ; Waterman-Storer and Salmon, 1999 ). Down-regulation of the MT destabilizer, stathmin/Op18, also enhances membrane ruffles in macrophage activation ( Xu and Harrison, 2015 ), supporting the idea that global stabilization of MTs disrupts polarity. The enhanced formation of random protrusions and membrane ruffling upon the depletion of MCAK indicates that MCAK might be involved in regional suppression of signals to prevent the formation of extra protrusions around the periphery, thus ensuring a dominant lamellipodial protrusion for efficient migration.…”
Section: Discussionmentioning
confidence: 74%
“…Consistent with this idea, stabilizing MTs by Taxol treatment leads to the formation of membrane protrusions evenly distributed around the cell perimeter rather than mainly at the cell front ( Schiff and Horwitz, 1980 ; Waterman-Storer and Salmon, 1999 ). Down-regulation of the MT destabilizer, stathmin/Op18, also enhances membrane ruffles in macrophage activation ( Xu and Harrison, 2015 ), supporting the idea that global stabilization of MTs disrupts polarity. The enhanced formation of random protrusions and membrane ruffling upon the depletion of MCAK indicates that MCAK might be involved in regional suppression of signals to prevent the formation of extra protrusions around the periphery, thus ensuring a dominant lamellipodial protrusion for efficient migration.…”
Section: Discussionmentioning
confidence: 74%
“…Down-regulation of the MT destabilizer, Stathmin/Op18, also enhances membrane ruffles in macrophage activation (Xu and Harrison, 2015), supporting the idea that global stabilization of MTs disrupts polarity. The enhanced formation of random protrusions and membrane ruffling upon the depletion of MCAK indicates that MCAK might be involved in regional suppression of signals to prevent the formation of extra protrusions around the periphery, thus ensuring a dominant lamellipodial protrusion for efficient migration.…”
Section: Discussionmentioning
confidence: 58%
“…STMN1 is a protein involved in cytoskeletal rearrangements that functions by binding to tubulin αβ heterodimers (microtubules), sequestering them and preventing microtubule assembly. The role of STMN1 on immune cells is contradictive, because its downregulation has been described as critical for microtubule stabilization and macrophage activation [ 60 ] and affects T cells polarization [ 61 ]. In our study, we found that over-expression of miR-221 and miR-210 could lead to downregulation of STMN1.…”
Section: Discussionmentioning
confidence: 99%